IMPROVEMENT OF MATHEMATICS LEARNING PROCESS AND OUTCOMES USING THE MAKE A MATCH MODEL ASSISTED BY CONGKLAK MEDIA IN GRADE III SDN 174/II APUNG ILIR: PENINGKATAN PROSES DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL MAKE A MATCH BERBANTU MEDIA CONGKLAK DI KELAS III SDN 174/II APUNG ILIR - Siti Nurhaliza; Nurlev Avana; Aldino Aldino (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research aims to improve the quality of the mathematics learning process and outcomes of grade III students of SDN 174/II Apung Ilir through the application of the Make a Match learning model assisted by congklak media. The method used is Class Action Research (PTK) which is carried out in two cycles, with each cycle including the stages of planning, implementation, observation, and reflection. Data collection is carried out through learning outcome tests, student activity observation sheets, and documentation. The results showed a significant increase in both indicators measured. The average score of student learning outcomes increased from 75.00 in the first cycle to 83.18 in the second cycle, with a learning completeness rate of 90.91%. Student activities also showed development, from the category of